Metacognitive and cognitive-behavioral interventions for psychosis: new developments . Issue 3 (30th September 2019) - Moritz, Steffen; Klein, Jan Philipp; Lysaker, Paul H.; Mehl, Stephanie
Abstract : This review describes four cognitive approaches for the treatment of schizophrenia: cognitive-behavioral therapy for psychosis (CBTp), metacognitive therapy, metacognitive training, and metacognitive reflection insight therapy (MERIT). A central reference point of our review is a seminal paper by James Flavell, who introduced the term metacognition ("cognition about cognition"). In a way, every psychotherapeutic approach adopts a metacognitive perspective when therapists reflect with clients about their thoughts. Yet, the four approaches map onto different components of metacognition. CBTp conveys some "metacognitive knowledge" (eg, thoughts are not facts) but is mainly concerned with individual beliefs. Metacognitive therapy focuses on unhelpful metacognitive beliefs about thinking styles (eg, thought suppression). Metacognitive training brings distorted cognitive biases to the awareness of patients; a central goal is the reduction of overconfidence. MERIT focuses on larger senses of identity and highlights metacognitive knowledge about oneself and other persons. For CBTp and metacognitive training, meta-analytic evidence supports their efficacy; single studies speak for the effectiveness of MERIT and metacognitive therapy.